Ecological risks of geological disasters and the patterns of the urban agglomeration in the Fujian Delta region. (June 2021) - Lin, Jinhuang; Lin, Mingshui; Chen, Wenhui; Zhang, An; Qi, Xinhua; Hou, Haoran
Highlights: A new 'hazard-vulnerability-exposure' three-dimensional evaluation system was constructed. Ecological risks of geological disasters show an trend of high in southeast and low in northwest. Ecological risks with 8 patterns was predominated by high population exposure. The combination of greater likelihood of inducing geological disasters was found. Abstract: Geological disasters not only hinder the ecological security guarantee in urban agglomerations, but also pose serious threat to the life and property of residents in the areas. The study establishes a "hazard-vulnerability-exposure" three-dimensional ecological risk assessment model, adopts an information value model to assess hazard, use landscape indices to analyze vulnerability and nighttime light data to indicate population exposure, and then quantitatively assesses the watershed-scale ecological risks of geological disasters and their patterns. The results show that ecological risks of geological disasters are mainly medium risks, presenting the trend of weakening from southeastern coastal areas to northwestern inland areas. The ecological risks exist in eight patterns in combination of the three dimensions of hazard, vulnerability and exposure. The elevation of 600–800 m, slope of 5 15°, aspect as southwest, NDVI of 0.4–0.6, lithology of metamorphic rocks, land use type as farmland, multi-year average precipitation of >1600 mm, distance to river of less than 200 m and distance to fault of less than 1000 m are the combination of greater likelihood of inducing geological disasters. The study finds that ecological risks of geological disasters show the trend of high in the southeast and low in the northwest and are the highest under combination of the high vulnerability and high exposure pattern out of the eight patterns that are predominated by high population exposure. In addition, the study discovers the combination of greater likelihood of inducing geological disasters, and puts forward the prevention and control measures against geological disasters in the future.